2008
DOI: 10.1037/0008-400x.40.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Examining the cross-race effect in lineup identification using Caucasian and First Nations samples.

Abstract: This study examined whether findings from research on the cross-race effect (CRE) in eyewitness memory with Caucasian-Black samples can be generalised to Caucasian-First Nations pairings in a lineup idenliflcation task. This study used a novel approach to investigate the CRE. using six targets, as well as simultaneous lineups that included both target-present atid target-absent arrays. This study also addressed the efficacy of the contact hypothesis as it applies to these populations. A significant CRE was dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 35 publications
(50 reference statements)
7
30
0
Order By: Relevance
“…It is important to note that other studies from our laboratory (Jackiw et al, 2008) have demonstrated the traditional CRE when using a lineup recognition paradigm, but in the absence of other semantic information being provided at encoding. As a result, we believe that our No Information condition was inconsistent with more traditional attempts to asses the CRE.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It is important to note that other studies from our laboratory (Jackiw et al, 2008) have demonstrated the traditional CRE when using a lineup recognition paradigm, but in the absence of other semantic information being provided at encoding. As a result, we believe that our No Information condition was inconsistent with more traditional attempts to asses the CRE.…”
Section: Discussionmentioning
confidence: 96%
“…No designated 'innocent suspect' was chosen for the target-absent lineups, such that analyses focused upon the aggregate rate of false alarm responses to foils in such arrays (cf. Jackiw et al, 2008;Meissner, Tredoux et al, 2005). No foils (non-target faces) were repeated across lineups, including the target-absent and target-present lineups for a given face.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paradigm differs from the more traditional eyewitness identification task by providing multiple identification opportunities to participants across both target-present and target-absent arrays, yet in doing so it also provides an opportunity to test theory using a variety of process measures. The paradigm has been used to examine lineup presentation factors (Meissner et al, 2005), carryover effects from show-ups to lineups (Haw, Dickinson, & Meissner, 2007), the cross-race effect (Evans, Marcon, & Meissner, in press;Jackiw, Arbuthnott, Pfeifer, Marcon, & Meissner, 2008) and the relationship between memory for contextual details and identification accuracy (Lane, Groft, Roussel, & Calamia, 2008).…”
Section: Eyewitness Research Examplesmentioning
confidence: 99%